Exploiting Combinatorics to Investigate Plasmonic Properties in Heterogeneous AgAu Nanosphere Chain Assemblies. Issue 9 (24th February 2021) - Schletz, Daniel; Schultz, Johannes; Potapov, Pavel L.; Steiner, Anja Maria; Krehl, Jonas; König, Tobias A. F.; Mayer, Martin; Lubk, Axel; Fery, Andreas
Abstract: Chains of coupled metallic nanoparticles are of special interest for plasmonic applications because they can sustain highly dispersive plasmon bands, allowing strong ballistic plasmon wave transport. Whereas early studies focused on homogeneous particle chains exhibiting only one dominant band, heterogeneous assemblies consisting of different nanoparticle species came into the spotlight recently. Their increased configuration space principally allows engineering multiple bands, bandgaps, or topological states. Simultaneously, the challenge of the precise arrangement of nanoparticles, including their distances and geometric patterns, as well as the precise characterization of the plasmonics in these systems, persists. Here, the surface plasmon resonances in heterogeneous AgAu nanoparticle chains are reported. Wrinkled templates are used for directed self‐assembly of monodisperse gold and silver nanospheres as chains, which allows assembling statistical combinations of more than 10 9 particles. To reveal the spatial and spectral distribution of the plasmonic response, state‐of‐the‐art scanning transmission electron microscopy coupled with electron energy loss spectroscopy accompanied by boundary element simulations is used. A variety of modes in the heterogeneous chains are found, ranging from localized surface plasmon modes occurring in single gold or silver spheres, respectively, to modes that result from the hybridization of the single particles. This approach opens a novel avenue toward combinatorial studies of plasmonic properties in heterosystems. Abstract : Heterogeneous chains of plasmonic particles are promising structures for engineering waveguiding properties of plasmonic structures. In this work, heterogeneous particle chains composed of gold and silver spheres are stochastically assembled, virtually generating every possible combination up to a length of 17. Their plasmonic properties are investigated by electron energy loss spectroscopy and boundary element simulations.